Evolution of hypervirulence by a MRSA clone through acquisition of a transposable element. Issue 4 (16th July 2014) - Benson, Meredith A.; Ohneck, Elizabeth A.; Ryan, Chanelle; Alonzo, Francis; Smith, Hannah; Narechania, Apurva; Kolokotronis, Sergios‐Orestis; Satola, Sarah W.; Uhlemann, Anne‐Catrin; Sebra, Robert; Deikus, Gintaras; Shopsin, Bo; et al.
Summary S taphylococcus aureus has evolved as a pathogen that causes a range of diseases in humans. There are two dominant modes of evolution thought to explain most of the virulence differences between strains. First, virulence genes may be acquired from other organisms. Second, mutations may cause changes in the regulation and expression of genes. Here we describe an evolutionary event in which transposition of an IS element has a direct impact on virulence gene regulation resulting in hypervirulence. Whole‐genome analysis of a methicillin‐resistant S. aureus (MRSA) strain USA500 revealed acquisition of a transposable element (IS256) that is absent from close relatives of this strain. Of the multiple copies of IS256 found in the USA500 genome, one was inserted in the promoter sequence of repressor of toxins (Rot), a master transcriptional regulator responsible for the expression of virulence factors in S. aureus. We show that insertion into the rot promoter by IS256 results in the derepression of cytotoxin expression and increased virulence. Taken together, this work provides new insight into evolutionary strategies by which S. aureus is able to modify its virulence properties and demonstrates a novel mechanism by which horizontal gene transfer directly impacts virulence through altering toxin regulation.